Kualitas Pendidikan Dan Pola Asuh Orang Tua: Sebuah Tinjauan Multidisiplin - Siti Noor Aini; Jihan Jihan; Febritesna Nuraini; Saripuddin Saripuddin; Heri Gunawan (Departement of Mathematics Education, 2023)
Education is an important part of human life. Good or bad education can be seen based on the quality of education. As for determining the quality of good education, there are many factors that influence it. Parenting style is one of the factors that has an important role in determining the quality of education a child receives. This study then aims to look at how the relationship that is formed between the quality of education and parenting styles is viewed from a sociological and educational perspective. This type of research is descriptive qualitative research. The data used in this study comes from various research results and previous studies that still have a relationship with the discussion in this study. The results of this study then found that parenting style carried out by parents has a fairly important role in shaping the quality of children's education. Positive parenting styles can help children achieve success in their education. Adpaun parenting that is negative and unhealthy can actually improve the academic quality of children.